2013
DOI: 10.12720/jolst.1.4.196-200
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Producing Bacterium and its Enzyme Characterization

Abstract: Recently, renewable energy is very important use for industrial development, transport because it is environmental friendly and can reduce high cost of imported fossil fuel. The evolution of biodiesel production has been reported in many researchers. Transesterification process which is mainly reaction for biodiesel is required catalysts such as acid, base catalyst or biocatalyst. In this study, 134 isolates were selected from soil contaminated with oil in Khon Kaen region by using culture medium containing 1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…The colonies of lipase producing bacteria were showed halos of orange fluorescent during 48hrs of incubation at 37°C, This appearance may be due to the hydrolysis of substrate, or due to the construction of conjugate of a Rhodamine -B long chain fatty acid. The results in the present study agree with study of 21,13,[22][23][24][25][26] . Qualitative screening of Pseudomonas sp LSK25 lipase showed positive evidence of lipase production.…”
Section: Investigation Screening Of Lipase Producing Bacteriasupporting
confidence: 93%
“…The colonies of lipase producing bacteria were showed halos of orange fluorescent during 48hrs of incubation at 37°C, This appearance may be due to the hydrolysis of substrate, or due to the construction of conjugate of a Rhodamine -B long chain fatty acid. The results in the present study agree with study of 21,13,[22][23][24][25][26] . Qualitative screening of Pseudomonas sp LSK25 lipase showed positive evidence of lipase production.…”
Section: Investigation Screening Of Lipase Producing Bacteriasupporting
confidence: 93%
“…These results were more than that obtained from several researchers as Guzman and Virginia (2008) who detected lypolytic activity of 0.079 U/ml by Bacillus pumilus LV01 isolated from water samples and maximum lipase production of 12 U/ml by Pseudomonas gessardii selected from a soil sample (Veerapagu et al, 2013). These results were in accordance to Boonmahome and Mongkolthanaruk (2013) who found that Pseudomonas aeruginosa isolate NA37 selected from soil contaminated with oil in Khon Kaen region showed high lipase activity (190 mU/ml) detecting with p-nitrophenyl palmitate as a substrate. On the other hand, Dhiman and Chapadgaonkar (2013) isolated and identified as Bacillus ISC 1, from a site of regular oil spill, showed high lipase production of 25 U/ml.…”
Section: Screening Of Different Bacterial Isolates For Production Of Lipase Enzymesupporting
confidence: 92%
“…The results were reviewed after 48 h of incubation, time reported to allow better contact between substrate and strains (Feng et al, 2010;Boonmahome, 2013) and shown in Table 3, in which strain 12 presented the highest enzymatic activity with a halo diameter of 10.7 mm followed by strain 38 with 10.6 mm, both considered as good producers according to the criteria established by Hou and Johnston (1992). From the results of the statistical analysis (p<0.05), strains 12, 38, 35, 30 and 31 were selected for further study and given that from this analysis the selected strains were part of the same group, from spectrophotometric quantification, we were able to discern and stablish significant difference between them (data not shown).…”
Section: Lipasesmentioning
confidence: 99%